Dasar Statistika - Nasution, Leni Masnidar (Al-Fikru: Jurnal Ilmiah, 2019)
Statistics is a science that deals with scientific methods for the collection, organization, summary, presentation and analysis of data, and also uses methods for drawing valid conclusions. Statistics has a role in educational research because it can be a tool in the process of analyzing data obtained from the results of research conducted. This paper aims to assist researchers in finding samples so that researchers can work efficiently on the results found in accordance with the object under study, assisting researchers in reading data collected so that they can make the right decision, helping researchers in seeing differences and group relationships on the objects studied , can predict the time to come, and can interpret the data collected. The writing method used is qualitative. The findings of this paper can be used by users as an understanding to determine the decision to be taken from an intended event based on statistics.